Design and development of a building control system using power line and wireless communications - Lee, Edwin Jia Liang. (2009)
Power Line communications (PLC) has received tremendous attention in recent years as an alternative and costeffective technology. Its strength and popularity can be attributed to its ubiquitous nature and readily available infrastructure. The advantage of using power lines as a data transmission medium is that every building and home is already equipped with the power line and connected to the power grid. The power line carrier communication systems use the existing AC electrical wiring as the network medium to provide highspeed network access points almost anywhere when there is an AC outlet. Through PLC, data can be transmitted at broadband speed. Broadband Power Line Communications (BPLC) is useful in a huge building control system as data can be transmitted over longer distances. Data coverage can be further exploited with BPLC interfacing with wireless communication. Such technology is definitely very practical, convenient and cost saving as it uses the basic infrastructure of buildings. BPLC can be interfaced to an IEEE 802.11b/g wireless LAN access point to create a WiFi network in a building for surveillance purpose.